Services for the blind at the UM Library - Krishnan, B. (University of Malaya Library, 1984)
The University of Malaya included blind students in its intake for the first time in 1970. From then on, there has been an average of about 203 blind students at each annual intake. So far 21 have graduated and there are currently 9 students on campus, 3 of whom are pursuin Masters prorammes, 4 are doing degree in arts and 2 in law.The collection started with 21 titles in braille donated by the Royal National Institute for he Blind. These titles contained 66 bulky volumes. Subsequently gifts were received from RNIB which now total 934 volumes. Describes subsequent donations, equiomentsand facilities made available to the blind at the library.